2015
DOI: 10.1007/jhep07(2015)094
|View full text |Cite
|
Sign up to set email alerts
|

Holographic Hall conductivities from dyonic backgrounds

Abstract: We develop a general framework for computing the holographic 2-point functions and the corresponding conductivities in asymptotically locally AdS backgrounds with an electric charge density, a constant magentic field, and possibly non-trivial scalar profiles, for a broad class of Einstein-Maxwell-Axion-Dilaton theories, including certain Chern-Simons terms. Holographic renormalization is carried out for any theory in this class and the computation of the renormalized AC conductivities at zero spatial momentum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 117 publications
(256 reference statements)
2
74
0
Order By: Relevance
“…As discussed before, for mass functions satisfying the near-boundary asymptotics m( ) ∼ a , with a = 1 or a > 3/2, the asymptotic solution of the equation of motion for the 2-form field near the boundary is the same as the asymptotic solution for the Maxwell field, and one can easily show that the on-shell boundary action (2.22) remains finite in the limit → 0, such that one does not need to resort to the holographic renormalization procedure [23][24][25][26][27] in these cases, i.e, the boundary condition for the massive 2-form ensures that the on-shell action is finite at the boundary just like the Maxwell action is in the same dimensionality. Then, we can immediately obtain from (2.22) and (2.9) the expressions for the retarded Green's function and the associated conductivity, respectively:…”
Section: Jhep07(2015)070mentioning
confidence: 98%
See 1 more Smart Citation
“…As discussed before, for mass functions satisfying the near-boundary asymptotics m( ) ∼ a , with a = 1 or a > 3/2, the asymptotic solution of the equation of motion for the 2-form field near the boundary is the same as the asymptotic solution for the Maxwell field, and one can easily show that the on-shell boundary action (2.22) remains finite in the limit → 0, such that one does not need to resort to the holographic renormalization procedure [23][24][25][26][27] in these cases, i.e, the boundary condition for the massive 2-form ensures that the on-shell action is finite at the boundary just like the Maxwell action is in the same dimensionality. Then, we can immediately obtain from (2.22) and (2.9) the expressions for the retarded Green's function and the associated conductivity, respectively:…”
Section: Jhep07(2015)070mentioning
confidence: 98%
“…This general analytic result will also be useful as a consistency check of the numerical results for the AC conductivity in section 3. In order to compute the AC conductivity (2.24), we substitute the Ansatz (2.21) into (2.19) and define the following quantity 27) which obeys a first order ordinary differential equation [15] …”
Section: Jhep07(2015)070mentioning
confidence: 99%
“…where S GHY is the Gibbons-Hawking-York action [91,92] needed to establish a well-posed variational problem with Dirichlet boundary condition for the metric, and S CT is the counterterm action that can be constructed using the holographic renormalization procedure [93][94][95][96][97]. These two boundary terms contribute to the total on-shell action but not to the equations of motion and, since we shall not need to compute the total on-shell action in the present work, we do not need to worry about their explicit form here.…”
Section: Introductionmentioning
confidence: 99%
“…We now proceed to the study of the scalar boundary conditions allowed in our system, in light of the results of [53,54]. There it is shown that holographic renormalization acts as a canonical transformation: the boundary counterterms necessary for a well defined variational principle (and for the removal of divergences) are such that the symplectic map φ * of the modes is diagonal.…”
Section: Dual Field Theory Interpretationmentioning
confidence: 99%
“…We can then can use the procedure of [53] (see also [54]) and add a canonical counterterm S ct (69) which makes the symplectic map diagonal, giving…”
Section: Dual Field Theory Interpretationmentioning
confidence: 99%